2020
DOI: 10.1002/mds.28220
|View full text |Cite
|
Sign up to set email alerts
|

Laryngeal Movement Disorders in Multiple System Atrophy: A Diagnostic Biomarker?

Abstract: A BS TRACT: Background: Multiple system atrophy (MSA) is a rare neurodegenerative disorder, and its parkinsonian variant can be difficult to delineate from Parkinson's disease (PD). Despite laryngeal dysfunction being associated with decreased life expectancy and quality of life, systematic assessments of laryngeal dysfunction in large cohorts are missing. Objectives: The objective of this study was to systematically assess laryngeal dysfunction in MSA and PD and identify laryngeal symptoms that allow for diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 69 publications
(254 reference statements)
3
40
0
Order By: Relevance
“…22 In brief, we compared a cohort of patients with MSA (median, 64 [interquartile range (IQR): 59-71] years) with an age-matched cohort of patients with PD (median, 67 [IQR: 60-73] years; P = 0.06). Patients with MSA had a shorter disease duration (median, 4 [IQR: 3-5] vs. 7 [5][6][7][8][9][10] years; P < 0.0001), a higher disease severity (H&Y stage 4 [IQR: 3-4] vs. 3 [2][3][4]; P < 0.0001), and were physically more impaired (Unified Parkinson's Disease Rating Scale-motor, Part III: 35.5 [IQR: 29.8-41.8] vs. 28 [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]; P < 0.01; Table 1). Cerebral MRI scans of 49 patients with MSA were available for analysis to support the clinical diagnosis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…22 In brief, we compared a cohort of patients with MSA (median, 64 [interquartile range (IQR): 59-71] years) with an age-matched cohort of patients with PD (median, 67 [IQR: 60-73] years; P = 0.06). Patients with MSA had a shorter disease duration (median, 4 [IQR: 3-5] vs. 7 [5][6][7][8][9][10] years; P < 0.0001), a higher disease severity (H&Y stage 4 [IQR: 3-4] vs. 3 [2][3][4]; P < 0.0001), and were physically more impaired (Unified Parkinson's Disease Rating Scale-motor, Part III: 35.5 [IQR: 29.8-41.8] vs. 28 [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]; P < 0.01; Table 1). Cerebral MRI scans of 49 patients with MSA were available for analysis to support the clinical diagnosis.…”
Section: Resultsmentioning
confidence: 99%
“…In brief, this protocol is divided into an examination of laryngeal function at rest and during specific task performances followed by a detailed evaluation of swallowing. For the laryngeal assessment, please refer to the previous publications 21,22 . Swallowing was assessed as follows: during FEES, participants received 11 consecutive standardized test boluses in the following order: (1) 3 teaspoons of applesauce (approximately 3 mL each), (2) 1 teaspoon of blue‐dyed liquid (approximately 3 mL) to test oral control of a liquid bolus (task to hold a liquid bolus in the oral cavity until told to swallow), (3) 2 teaspoons of blue‐dyed water (approximately 3 mL), (4) one sip of blue‐dyed water from a glass or straw, (5) three pieces of buttered soft white bread (about 3‐cm square), and (6) one swallow of a placebo tablet (10‐mm diameter) ingested with either blue‐dyed water or applesauce.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For Warnecke et al [ 22 ], arytenoid fluttering or flapping and abduction defects are pathognomonic signs of MSA. This fact was corroborated by Gandor et al [ 23 ], who explained that arytenoid fluttering could serve as a biomarker to differentiate between MSA and PD. These studies also confirm the importance of stridor, already identified as a factor for a poor prognosis in Krim and Yekhlef’s study (RR = 3.64; p = 0.006) [ 24 ].…”
Section: Discussionmentioning
confidence: 52%
“…In all the cases with an undiagnosed underlying disease, detailed information on the anatomical, sensory-motor findings, and effects of compensatory strategies must be obtained and discussed with the physician or medical team in charge of the patient. In some cases, this information is pathognomonic for the underlying disease, such as the sign of the rising tide in case of a Zenker diverticulum [ 50 ], while in other cases, additional clinical information is necessary to determine the underlying diagnosis, such as a vocal fold movement disorder in multiple system atrophy [ 51 , 52 ].…”
Section: The Aim Of a Fees Examinationmentioning
confidence: 99%